The effect of school quality on educational attainment and wages - Lorraine Dearden; Javier Ferri; Costas Meghir (Institute for Fiscal Studies (IFS), 2000)
The paper examines the effects of school pupil-teacher ratios and type of school on educational attainment and wages using the British National Child Development survey (NCDS). The NCDS is a panel survey which has followed a cohort of individuals born in March 1958, and has a rich set of background variables recorded throughout the individual's life. The results suggest that, once we control for ability and family background, the pupil-teacher ratio has no impact on educational qualifications or on male wages. It has an impact on women's wages at the age of 33, particularly those of low ability. We also find evidence that those who attend selective schools have better educational outcomes and, in the case of men, higher wages at the age of 33. The impact is higher for the type of individuals who are less likely not to attend selective schools, but for whom a comparison group does exist among those attending.
Keywords: 330; Schule; Dienstleistungsqualität; Bildungsertrag; Bildungsniveau; Lohn; Großbritannien